ANALYSIS OF PRE-HEATING TEMPERATURE EFFECT ON SHIELDED METAL ARC WELDING (SMAW) OF BKI GRADE (KI-A) PLATES TO THE TENSILE STRENGTH AND HARDNESS - Erifive Pranatal; Noveta Fernaldinatan; Norita Prasetya Wardhani; Adi Kurniawan Yusim (Institut Teknologi Adhi Tama Surabaya, 2023)
This study aimed to analyze BKI Grade (KI-A) plate material using the pre-heat process to determine tensile strength and hardness. The method involved welding with shielded metal arc welding (SMAW) type. The pre-heat variations used several temperatures, such as 50â°C, 120â°C, 220â°C, and without heat treatment. The tensile strength obtained specimen without pre-heating had the lowest tensile strength of 442.64 MPa, and the specimen with pre-heating to 220â°C had the highest average tensile strength of 450.11 MPa. The result showed that tensile strength was proportional to the pre-heating temperatures given. The hardness observation found that the hotter the pre-heating temperature obtained, the higher the hardness value of the base metal and HAZ would obtain. It was different with weld metal which would decrease. From those two parameters, it could be concluded that the most optimal pre-heat temperature was 220â°C.